Analisis Evaluasi Kebun PlaAnalisis Evaluasi Kebun Plasma Yang Dikelola Oleh Kebun Inti Dan Dikelola Sendiri Oleh Peserta Plasma Terhadap Pendapatan Petani Kelapa Sawit (Kasus Pt. Pinago Utama, Kabupaten Musi Banyu Asin Provinsi Sumatera Selatan) - Zulkifly, Zulkifly; Lubis, Yusniar; Lubis, Syaifuddin (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2020)
This study aims to determine and analyze the differences and the effect of production on the income of plasma palm oil farmers who are independently managed and managed in the core of PT. Pinago Utama. This research method uses a quantitative approach, the type of research is a survey. The sample was determined by 60 stratified random sampling methods. Data were analyzed using the independent sample mean difference test and simple linear regression. The results showed that there was an insignificant difference in the production of oil palm smallholdings managed by nucleus and those managed independently by farmers. However, there are significant differences in farmers' incomes, production costs and the cost of production of plasma oil palm estates managed by the nucleus and those managed by farmers independently. The cost of production of the nucleus estate managed by the nucleus is Rp. 576.65 / kg 39.17% lower than smallholdings which are managed independently by farmers (Rp. 947.95 / kg). Changes in production obtained by farmers have a significant effect on changes in income, both for estates managed by the nucleus and those managed independently by farmers. Thus there is a difference in the effect of production on farmers' income by almost 50% (49.88%)